The Hydra-Headed Coronaviruses: Implications of COVID-19 for Homeopathy - Waisse, Silvia; Oberbaum, Menachem; Frass, Michael (Homeopathy, 2020)
Successful homeopathic prescriptions are based on careful individualization of symptoms, either for an individual patient or collectively in the case of epidemic outbreaks. The ongoing COVID-19 pandemic was initially represented as a severe acute respiratory illness, with eventual dramatic complications. However, over time it revealed to be a complex systemic disease with manifestations derived from viral-induced inflammation and hypercoagulability, thus liable to affect any body organ or system. As a result, clinical presentation is variable, in addition to variations associated with several individual and collective risk factors. Given the extreme variability of pathology and clinical manifestations, a single, or a few, universal homeopathic preventive Do not split medicine(s) do not seem feasible. Yet homeopathy may have a relevant role to play, inasmuch as the vast majority of patients only exhibit the mild form of disease and are indicated to self-care at home, without standard monitoring, follow-up, or treatment. For future pandemics, homeopathy agencies should prepare by establishing rapid-response teams and efficacious lines of communication.
Keywords: coronavirus diseases; homeopathy; therapeutic approaches; complex pandemics